Soft Skills vs Technical Skills: A Narrative Literature Review on the Determinants of Work Readiness Among Recent Graduates - Atina Ainun Mardiyah; Ainul Hayat (Jurnal Indonesia Sosial Sains, 2026)
This study analyzes the role of soft and technical skills in determining the employability of new graduates by addressing three main questions: which soft skills are most influential, which technical skills are most needed, and which skills dominate based on global evidence. A narrative literature review design was employed, with systematic searches of eight academic databases (Scopus, Google Scholar, ScienceDirect, Taylor & Francis, SAGE, Elsevier, Elicit, and SINTA) conducted during October–November 2024. Following a rigorous screening process, 25 peer-reviewed articles published between 2020 and 2025 and focusing on final-year students or recent graduates (within 1–3 years post-graduation) were selected for analysis. The study revealed that employability is shaped by a balance of technical competence and adaptive ability, aligning with the employability framework as a psychosocial construct. Soft skills—such as communication, collaboration, self-management, and problem-solving—were found to be more dominant in facilitating graduates' adaptation and early performance. Meanwhile, technical skills served as a prerequisite for entry-level positions. The study also highlighted differences in skill requirements between STEM and non-STEM fields: STEM fields prioritized technical expertise, while non-STEM fields focused more on interpersonal skills. The findings suggest that integrating both soft and technical skills through project-based, experiential, and work-integrated learning is the most effective strategy to enhance job readiness. The practical implications stress the importance of designing higher education curricula that balance technical competence with character and social skills, ensuring graduates are adaptive and competitive in the job market.